2016
DOI: 10.1016/j.scienta.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary studies of genom-wide association mapping for some selected morphological characters of watermelons

Abstract: Developing more efficient tools for watermelon (Citrullus lanatus (Thunb.) Matsum. & Nakai) breeding programs may greatly contribute to genetic improvement. The aims of this study were to investigate genome-wide association analysis (GWAS), and to develop regression models for some important watermelon traits such as yield, fruit weight, flesh color, total soluble solid, seed coat color, seed length and flowering time using 96 lines selected from 258 pure lines. An initial analysis was conducted to reduce samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It also identified two SNPs on chromosome 1 as being responsible for the PA phenotype. GWAS was used to map other important agronomic traits in watermelon, melon and cucumber ( Nimmakayala et al, 2016 ; Yagcioglu et al, 2016 ; Dou et al, 2018a ; Dou et al, 2018b ; Hou et al, 2018 ; Wang et al, 2018 ; Bo et al, 2019b ; Bo et al, 2019a ; Oren et al, 2019 ). The major sex-determining gene for monoecy/andromonoecy in melon ( CmACS7 ) was also successfully detected using the GWAS approach ( Gur et al, 2017 ; Zhang H. et al, 2019 ), but so far no other andromonoecy locus had been found in cucurbits.…”
Section: Discussionmentioning
confidence: 99%
“…It also identified two SNPs on chromosome 1 as being responsible for the PA phenotype. GWAS was used to map other important agronomic traits in watermelon, melon and cucumber ( Nimmakayala et al, 2016 ; Yagcioglu et al, 2016 ; Dou et al, 2018a ; Dou et al, 2018b ; Hou et al, 2018 ; Wang et al, 2018 ; Bo et al, 2019b ; Bo et al, 2019a ; Oren et al, 2019 ). The major sex-determining gene for monoecy/andromonoecy in melon ( CmACS7 ) was also successfully detected using the GWAS approach ( Gur et al, 2017 ; Zhang H. et al, 2019 ), but so far no other andromonoecy locus had been found in cucurbits.…”
Section: Discussionmentioning
confidence: 99%